The courage of truth and ethopolitical parresia. Over the historical category of cynicism - Rodríguez Rojas, Juan Manuel (2025)
There are many analyzes that have been carried out in the latest works of Michel Foucault’s thinking. People have seen in them a critical proposal to contemporary forms of subjection and people have observed that this proposal has served neoliberalism to produce new subjective forms. This article analyzes Foucault’s last course at the College of France The courage of the truth with the aim of seeing it as the final effort of the thinker to propose a subjective form that contrasts with the ways of capturing neoliberalism and which this cannot appropriate it. In this reading, it is defined that the Foucauldian heritage, in addition to bequeathing a form of analysis of power that has been very fruitful (biopolitics), also links us to the need to follow subjective forms of thought against the dynamics of actual power that will never end captured or appropriated.